Comparative study on the performance and phenotypic characteristics of indigenous chickens in Purwokerto and Dili - Tugiyanti, Elly; Muatip, Krismiwati; Ulfah, Annistia R.; Ximenes, Neotico Dias da Gama; Alfonso, Armando (Journal of Advanced Veterinary Research, 2026)
Poultry settles and adapts to environments that allow them to live and reproduce. Timor Leste has a dry tropical climate with temperatures ranging from 24-34°C and low rainfall. In contrast, Indonesia has a tropical climate with daily temperatures ranging from 23-29°C and relatively higher rainfall compared to Timor Leste, although this depends on the location. These environmental differences allow local chickens to develop differently. This research was conducted using a purposive sampling data collection method, involving qualitative and quantitative observations of local chickens in Indonesia and Timor Leste. The number of local chickens measured was 40 female local chickens aged 10-12 months, 40 female local chickens aged 13-15 months, and 10 male chickens raised in open areas by the community in Dili, Timor Leste, as well as by the community in Purwokerto, Indonesia. The measured variables are body weight, carcass weight, digestive organ size, and qualitative characteristics (feather color, comb color and type, beak color, eye color, and leg color). Data from both areas were then tabulated and described descriptively. Local chickens from Purwokerto (Indonesia) and Dili (East Timor) showed significant differences in body and carcass weight, with Indonesian chickens being heavier. Despite being geographically separated, their digestive organ profiles are very similar, indicating comparable digestive functions. However, phenotypic traits such as feather color, comb type and color, and beak, eye, and leg color vary greatly within both populations, likely due to different breeding histories and genetic introductions.